INSTAGRAM VS TIKTOK: A COMPARATIVE STUDY OF CONTENT STRATEGIES TO ENHANCE ENGAGEMENT AND BRAND AWARENESS OF TOMORO COFFEE IN MEDAN - Muhammad Arief Rachman; Martha Tri Lestari (International Journal of Cultural and Social Science, 2025)
This study compares the effectiveness of Instagram and TikTok content strategies in enhancing engagement and brand awareness for Tomoro Coffee in Medan, Indonesia. A qualitative case study approach was used, employing the Circular Model of SoMe (Share, Optimize, Manage, Engage) as the analytical framework. Data were gathered through content analysis, interviews with brand representatives, and observations at 10+ outlets. Findings show that Instagram builds consistent brand identity through curated storytelling, while TikTok drives user engagement via viral content. However, centralized content production and lack of local customization reduce emotional resonance in regional markets. The study concludes that Instagram supports long-term branding, while TikTok aids rapid visibility. Recommendations include decentralizing content creation, involving local teams, and aligning strategies with local culture.